A Study On The Purpose Of 3d Visualization Software In Education For Creative And 2technical Subjects - Jinghai, Zhou; Doraisamy Pillai, Muralitharan (Journal of Neonatal Surgery, 2025)
In what ways might 3D visualization tools benefit students with both technical and creative backgrounds? This quantitative study is aimed at achieving that goal. The evaluations were conducted using both pre- and post-intervention questionnaires, feedback forms, and engagement surveys. Using 3D visualisation software had a substantial positive effect on students' academic performance; their test scores, on average, were 22% higher than those of the control group. Not only that, but the number of participants skyrocketed; after that, 84% of the experimental group said they were much more invested in the subject. The program was successful in improving students' understanding of complex concepts, as shown by a 30% increase in evaluations of conceptual clarity. Teachers and students alike reported improvements in spatial reasoning, ideation, and technical data memory after using the 3D visualisation tools. According to the study, the app was most effective in the engineering and design industries, which rely heavily on detailed visual representations. Lastly, quantitative studies have shown that the use of 3D visualisation software in the classroom has a significant positive impact on both the technical and creative fields. Academic performance, engagement, and comprehension all improve. Integration of such technology into educational activities has the potential to enhance a range of pedagogical techniques and learning results, according to the study.